A method for testing the pc content in pc alloys

CN117990879BActive Publication Date: 2026-11-03NAT POLYMER MATERIALS IND INNOVATION CENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410101273.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-24
Publication Date
2026-11-03
Estimated Expiration
2044-01-24

AI Technical Summary

Technical Problem

Existing methods for detecting PC content in PC alloys suffer from low accuracy, cumbersome operation, and narrow applicability, especially in PC alloy systems with complex compositions.

Method used

The sample to be tested was depolymerized using a microwave alcoholysis step. The PC alloy sample was depolymerized under microwave conditions using a specific diol and catalyst. The PC content was then confirmed using a comprehensive analytical method such as PyGC-MS, GC-FID, GC-MS, HPLC, LC-MS, TGA, and ICP-OES.

Benefits of technology

It achieves accurate detection of PC content in PC alloys with high accuracy, wide applicability, simple operation, and an error of less than 3%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117990879B_ABST
    Figure CN117990879B_ABST
Patent Text Reader

Abstract

The application discloses a method for testing PC content in PC alloy and belongs to the technical field of detection. The method is characterized by a specific microwave alcoholysis step for depolymerization treatment of a sample to be detected. The sample after the treatment can be detected and confirmed for PC content according to actual conditions by using various comprehensive methods. The testing method has high accuracy, simple sample preparation and detection operation, and is suitable for various PC alloys.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of detection technology, and specifically to a method for testing the PC content in PC alloys. Background Technology

[0002] PC alloys are high-performance plastic alloy materials synthesized from PC (polycarbonate) resin and other copolymers. Common PC alloys include PC / ABS alloys, PC / PE (polyethylene) alloys, and PC / PP (polypropylene) alloys. In current testing methods, the dissolution extraction method is generally used for qualitative and quantitative analysis of the components in plastic alloys. However, because the solubility of PC and another copolymer in these existing PC alloys is similar, it is difficult to implement the dissolution method for detection.

[0003] Therefore, based on the characteristics of PC alloys, researchers have further developed detection methods such as FTIR, TGA, and PyGC-MS for the quantification of PC. Among them, FTIR identifies the chemical structure of the resin by analyzing infrared spectra, and selects the absorption peaks of characteristic functional groups of PC resin and another copolymer (such as the ester peak of PC resin at 1773 cm⁻¹ in PC / ABS alloys). -1 And the styrene characteristic peak at 700 cm⁻¹ in ABS resin -1 By using standard samples of different proportions and applying Lambert-Beer's law, a quantitative model is established to determine the relationship between absorbance or the ratio of absorbance and concentration. The TGA method analyzes the content of different resins by measuring the mass change of the material during the heating process, and infers the PC content by comparing the amount of residual carbon in the sample with the amount of residual carbon in pure PC. The PyGC-MS method uses gas chromatography-mass spectrometry to qualitatively and quantitatively analyze resin components, and establishes a corresponding characteristic quantitative model by selecting characteristic fragments at the optimal pyrolysis temperature.

[0004] However, these three methods still have certain limitations, especially in terms of accuracy, which needs to be improved: FTIR has high requirements for sample preparation and cannot be well applied to PC alloy systems with complex compositions (especially those with a large number of functional groups); TGA cannot be applied to the quantitative analysis of some flame-retardant PC alloy systems because the residual carbon content of flame-retardant PC alloys fluctuates greatly; the injection volume of PyGC-MS is generally only between 0.1 and 0.3 mg, resulting in poor sample representativeness. Furthermore, taking PC / ABS alloys as an example, the ABS copolymer contained in them is polymerized from ternary monomers. In actual testing, the matching of the relative content of ABS monomers in the standard sample and the tested sample, as well as the differences between PC and ABS in different ratio ranges, all need to be considered, and different specific steps need to be used for detection. Although some technical solutions attempt to use inert solid powder as a dispersant for PC alloy samples and employ pyrolysis / gas chromatography-mass spectrometry for qualitative and quantitative analysis, establishing a calibration curve based on the relationship between the styrene peak area (a characteristic ABS pyrolysis product) and ABS content, and calculating the mass fraction of ABS in the PC / ABS mixture to further deduce the mass fraction of PC, this method cannot be applied to the detection of PC alloys containing styrene-based toughening agents. Therefore, existing methods for detecting PC content in PC alloys still suffer from technical bottlenecks such as low accuracy, cumbersome operation, and narrow applicability. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a method for testing the PC content in PC alloys. This method involves depolymerizing the sample through a specific microwave alcoholysis step. The treated sample can then be tested using various comprehensive methods to confirm the PC content. This testing method is highly accurate, easy to prepare and test, and applicable to various PC alloys.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] A method for testing the PC content in a PC alloy includes the following steps:

[0008] (1) The formulation system of the PC alloy sample to be tested is confirmed by infrared testing or XRF (X-ray fluorescence spectroscopy); the formulation system contains PC resin, compound resin and antioxidant;

[0009] (2) The PC alloy sample to be tested was placed in a diol containing a catalyst and subjected to alcoholysis catalytic depolymerization at 180-235℃ for 10-65 min under microwave conditions. The mixture was then filtered to obtain a mixed solution.

[0010] (3) Comprehensive analysis: The mixture is subjected to quantitative analysis of other additives besides PC depolymerization products. Through comprehensive analysis, the content of PC and other additives in the PC alloy is tested.

[0011] Preferably, the comprehensive analysis includes at least one of PyGC-MS testing, GC-FID testing, GC-MS testing, HPLC testing, LC-MS testing, TGA testing, and ICP-OES testing.

[0012] More preferably, the comprehensive analysis steps are as follows: statistically analyze the mass of the PC alloy sample before and after alcoholysis catalytic depolymerization, calculate the content of substances dissolved in the mixture of the PC alloy sample, detect the content of other additive substances other than PC depolymerization products by HPLC and / or LC-MS testing, and finally calculate the PC content in the PC alloy sample.

[0013] More preferably, the PC alloy sample to be tested is at least one of virgin material and recycled material.

[0014] More preferably, the mass content of PC in the PC alloy sample to be tested is ≥5wt%.

[0015] More preferably, the mass content of PC in the PC alloy sample to be tested is 5-95 wt%.

[0016] In existing technologies, the process of separating PC from PC alloys by dissolution is quite common, and the types and conditions of dissolving reagents used are also diverse. However, when the PC alloy contains not only PC resin but also compounded alloy resins and some functional small molecule additives, the complexity of the PC alloy composition increases. Conventional dissolution methods may result in insufficient PC dissolution or the presence of various impurities in the resulting solution that affect accuracy (especially in PC / ABS alloys, where PC and ABS exhibit similar organic solvent solubility). This ultimately necessitates multiple impurity removal steps for subsequent processing. Furthermore, most PC alloys contain small molecule antioxidants with numerous functional groups. Over time, these antioxidants gradually deteriorate and become ineffective. Conventional detection methods may even affect the accuracy of PC content detection. In the method described in this invention, after confirming the formulation of the sample (confirming whether the sample contains PC and the complexity of the formulation to facilitate the selection of appropriate methods or combinations in subsequent comprehensive quantitative analysis of PC), the inventors use a specific high-temperature alcoholysis catalytic depolymerization treatment under microwave conditions to remove PC from the sample. This method dissolves PC and certain specific soluble components. Compared to conventional low-temperature PC alcoholysis processes (existing PC alcoholysis processes generally use 100°C for low-temperature treatment and only dissolve, not depolymerize, PC), or processes using other solvents (such as chloroform) to dissolve PC, this treatment method ensures that only PC and a small amount of special components (such as flame retardants and trace amounts of processing aids like alcohol-soluble lubricants) can dissolve in the mixture. Components that significantly affect PC content detection, such as alloy copolymers (in PC / ABS alloys), are dissolved in the solution. ABS, toughening agents, fillers, etc., can be directly removed by filtration because they are insoluble. Since the basic components of the resulting mixture are the depolymerization products of PC, the content of other non-PC components is confirmed by conventional methods such as HPLC. Finally, the PC content is calculated by adding or subtracting mass. This process does not require the preparation of new standard samples (if new standard samples are prepared, multiple settings are required for different degrees of depolymerization of PC alloy, and the mixture needs to be separated), nor does it require any additional special treatment (such as considering the influence of the proportion of antioxidants). The error between the detected PC content and the actual content does not exceed 3%.

[0017] Meanwhile, this method has been verified to be applicable to recycled PC and prepared PC alloy products, and it can still be accurate as long as the true PC content in the sample is not less than 5 wt%, making it widely applicable.

[0018] Preferably, the compounded resin is at least one of ABS resin, PE resin, PP resin, POM resin, and PS resin.

[0019] Preferably, the PC alloy is at least one of PC / ABS alloy, PC / PE alloy, PC / PP alloy, PC / POM alloy, and PC / PS alloy.

[0020] It has been verified that the method for testing the PC content in PC alloys described in this invention is not limited to typical PC / ABS alloys, but is also applicable to some PC alloys with similar properties.

[0021] Preferably, in step (1), the specific method for infrared testing is as follows: the alloy sample to be tested is prepared by hot pressing to form a film, and then infrared detection and analysis are performed, with the wavenumber range being 400–4000 cm⁻¹. -1 The resolution is 3-5cm. -1 The number of infrared scans is 16 to 32.

[0022] Preferably, the diol is at least one of ethylene glycol, butanediol, and 1,2-propanediol; more preferably, it is at least one of ethylene glycol, butanediol, and 1,2-propanediol.

[0023] Compared to monools, diols have milder reaction conditions and do not require high pressure. They also have lower depolymerization temperatures than polyols and do not dissolve other substances, thus reducing processing difficulty. They are more effective at depolymerizing PC and are more suitable for the method described in this invention.

[0024] More preferably, the mass ratio of the diol to the PC alloy sample to be tested is (5-42):1.

[0025] More preferably, the mass ratio of the diol to the PC alloy sample to be tested is within the range of one or both of the following: 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 42:1.

[0026] Preferably, the catalyst used in the alcoholysis catalytic depolymerization is at least one selected from zinc acetate, potassium acetate, tetrabutyl titanate, sodium carbonate, sodium hydroxide, zinc oxide, and potassium hydroxide.

[0027] More preferably, the mass ratio of the catalyst to the PC alloy sample to be tested is (0.001 to 0.01): 1.

[0028] Preferably, the temperature for the alcoholysis catalytic depolymerization is 190–220°C, and the time is 30–60 min.

[0029] Preferably, the power of the microwave is 500 to 1000 W.

[0030] Preferably, the test conditions for the HPLC test are as follows:

[0031] Column: Waters Symmetry C18;

[0032] Column temperature: 30~40℃;

[0033] Flow rate: 0.5–1.5 mL / min;

[0034] Injection volume: 8–12 μL;

[0035] Mobile phase A is methanol, and mobile phase B is water;

[0036] The mobile phase isocratic elution program is: 90.0% methanol, 10.0% water.

[0037] Preferably, the test conditions for the GC-MS test are as follows: DB-5MS (30m×250μm×0.25μm), injection port temperature 270~290℃, and the temperature program is to hold at an initial temperature of 85~95℃ for 2~4min, and then raise the temperature to 315~325℃ at a heating rate of 18~22℃ / min and hold for 4~6min.

[0038] Flow rate: 1.4–1.6 mL / min, splitless;

[0039] Mass spectrometry conditions: Ion source temperature 228–232 °C, ionization mode EI; quadrupole temperature 145–155 °C; acquisition type: SIM and full scan, scan range mass number 50–800 amu; solvent delay 3.5–4.5 min, NIST 2017 mass spectrometry library.

[0040] The beneficial effects of this invention are that it provides a method for testing the PC content in PC alloys. This method uses a specific microwave alcoholysis step to depolymerize the sample to be tested. The treated sample can then be tested using various comprehensive methods to confirm the PC content according to the actual situation. This testing method has high accuracy, simple sample preparation and testing operation, and is applicable to various PC alloys. Attached Figure Description

[0041] Figure 1 The infrared spectra of the sample to be tested in the method described in Example 1 of the present invention are as follows: before (top) alcoholysis catalytic depolymerization and after alcoholysis catalytic depolymerization, the remaining insoluble matter is shown below.

[0042] Figure 2 The infrared spectra of the sample to be tested in the method described in Example 2 of this invention are as follows: before (top) alcoholysis catalytic depolymerization and after alcoholysis catalytic depolymerization, the remaining insoluble matter is shown below.

[0043] Figure 3The infrared spectra of the recycled PC / ABS sample before (top) and after (bottom) alcoholysis catalytic depolymerization are shown in Example 2 of the present invention. Detailed Implementation

[0044] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments and comparative examples. The purpose of this description is to provide a detailed understanding of the invention, not to limit its scope. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention. Unless otherwise specified, the experimental reagents and instruments involved in the implementation of this invention are commonly used reagents and instruments.

[0045] In specific embodiments of the present invention, to verify the accuracy and applicability of the method for testing the PC content in PC alloys described herein, various PC alloys were used as test samples, including:

[0046] PC / ABS Alloy 1: Composed of the following components by mass: 65% PC1, 29.8% ABS, 5% toughening agent S2501, and 0.2% antioxidant.

[0047] PC / ABS Alloy 2: Composed of the following components by mass: 72% PC1, 14.8% ABS, 5% toughening agent S2501, 8% triphenyl phosphate (TPP flame retardant), and 0.2% antioxidant.

[0048] PC / ABS Alloy 3: Composed of the following components by mass: 72% PC1, 14.8% ABS, 5% toughening agent S2501, 8% bisphenol A bis(diphenyl phosphate) (BDP flame retardant), and 0.2% antioxidant.

[0049] PC / ABS Alloy 4: Composed of the following components by mass: 65% PC2, 29.8% ABS, 5% toughening agent S2501, and 0.2% antioxidant.

[0050] PC / ABS Alloy 5: Composed of the following components by mass: 10% PC1, 80% ABS, 10% toughening agent MBS, and 0.2% antioxidant.

[0051] PC / PE alloy: Composed of the following components by mass: 85% PC1, 10% LDPE, 5% LDPE-g-MAH, and 0.2% antioxidant.

[0052] PC / PS alloy: Composed of the following components by mass: 85% PC1, 10% PS, 5% SBS-g-MAH, and 0.2% antioxidant.

[0053] Recycled PC / ABS alloy: Composed of the following components by mass: 75% recycled PC, 24.8% ABS, and 0.2% antioxidant.

[0054] In the specific embodiments of the present invention, each PC alloy is prepared by direct mixing and melt extrusion using a twin-screw extruder. The melt extrusion temperature of the twin-screw extruder is 240-275°C, and the screw speed is 880 r / min.

[0055] The PC1 is an S-2000F manufactured by Mitsubishi Corporation of Japan, and its melt mass flow rate at 300°C and 1.20 kg load, as tested according to ISO 1133-2022, is 10 g / 10 min.

[0056] The PC2 mentioned is PC 2600 produced by Wanhua Chemical, and its melt mass flow rate at 300℃ and 1.20kg load, as tested according to ISO 1133-2022, is 60g / 10min.

[0057] The recycled PC is PC ASL-06 produced by Shanghai Xiaoyue Industrial Co., Ltd., and its melt flow rate at 300℃ and 1.20kg load, as tested according to ISO 1133-2022, is 9g / 10min.

[0058] The ABS used is ABS275 manufactured by Shanghai Gaoqiao, and its melt flow rate is 2.6 g / 10 min at 200℃ and 3.8 kg load, as tested according to ASTM D-1238.

[0059] The toughening agent S2501 is S2501 manufactured by Mitsubishi Corporation of Japan, and is an organosilicon toughening agent.

[0060] The toughening agent MBS is EM-500 manufactured by LG Chem.

[0061] The flame retardant is commercially available triphenyl phosphate and bisphenol A-bis(diphenyl phosphate).

[0062] The antioxidant is a mixture of antioxidant 1076 (IRGANOX 1076) and antioxidant 168 (RIANOX 168) in a mass ratio of 1:1.

[0063] The LDPE mentioned is LDPE 2420F produced by CNOOC Shell Petrochemicals Co., Ltd.

[0064] The LDPE-g-MAH is E528 manufactured by DuPont.

[0065] The PS mentioned is GPPS MC 3100 produced by Yashide (Jiangsu) Chemical Co., Ltd.

[0066] The method for calculating the relative deviation of PC content in the various embodiments, control group, and comparative examples of the present invention is as follows:

[0067] Relative deviation = (PC content test value - PC content theoretical value) / PC content theoretical value * 100%.

[0068] Example 1

[0069] The embodiment of the present invention for testing the PC content in PC alloys, the method for testing the PC content in PC alloys, includes the following steps:

[0070] (1) The formulation system of the PC / ABS alloy 1 sample to be tested was confirmed by infrared and XRF testing. The system contains PC, ABS and Si elements. For infrared testing, the sample was prepared by hot pressing film formation method, and then infrared detection and analysis were performed. The wavenumber range of the analysis was 400 to 4000 cm⁻¹. -1 The resolution is 3-5cm. -1 The number of infrared scans was 16.

[0071] (2) Place 1.0888g of sample into 40g of 1,4-butanediol under microwave conditions of 500-1000W (automatic adjustment) at 220℃ for catalytic depolymerization for 30min, filter, and obtain a mixture and insoluble matter; add zinc acetate for catalytic depolymerization, with the mass ratio of zinc acetate to sample being 0.005:1;

[0072] (3) Comprehensive analysis: The insoluble matter was washed and filtered with methanol multiple times, dried, and weighed to 0.3627g. Infrared spectroscopy confirmed complete depolymerization and separation of PC. The PC content could be obtained by subtracting the weight difference, thus completing the test of PC content in the PC alloy.

[0073] Example 2

[0074] The embodiment of the present invention for testing the PC content in PC alloys, the method for testing the PC content in PC alloys, includes the following steps:

[0075] (1) The formulation system of the PC / ABS alloy sample 2 to be tested was confirmed by infrared and XRF testing. The system contains PC, ABS, Si and P elements. For infrared testing, the sample was prepared by hot pressing film formation method, and then infrared detection and analysis were performed. The wavenumber range of the analysis was 400 to 4000 cm⁻¹. -1 The resolution is 3-5cm. -1 The number of infrared scans was 16.

[0076] (2) Place 1.0697g of sample into 40g of ethylene glycol under microwave conditions of 500-1000w (automatic adjustment) at 190℃ for catalytic depolymerization for 60min, filter, and obtain a mixture and insoluble matter; add tetrabutyl titanate for catalytic depolymerization, the mass ratio of tetrabutyl titanate to sample is 0.001:1;

[0077] (3) Comprehensive analysis: The insoluble matter was washed repeatedly with methanol, filtered, dried, and weighed to 0.2189 g. Infrared spectroscopy confirmed complete depolymerization and separation of PC. The mixture was subjected to GC-MS and HPLC tests to detect the qualitative and quantitative analysis of other additives besides the PC depolymerization products, namely the flame retardant phosphate ester. The PC content was obtained by subtracting the flame retardant component from the soluble component, thus completing the test of PC content in the PC alloy.

[0078] The quantitative analysis of PC was performed by GC MS and HPLC.

[0079] The test conditions for HPLC testing are as follows:

[0080] Column: Waters Symmetry C18;

[0081] Column temperature: 30~40℃;

[0082] Flow rate: 0.5–1.5 mL / min;

[0083] Injection volume: 8–12 μL;

[0084] Mobile phase A is methanol, and mobile phase B is water;

[0085] The mobile phase isocratic elution program is: 90.0% methanol, 10.0% water.

[0086] The GC-MS test conditions were as follows: DB-5MS (30m × 250μm × 0.25μm), injection port temperature 280℃, temperature program: hold at an initial temperature of 90℃ for 3 min, then increase to 320℃ at a rate of 20℃ / min and hold for 5 min. Flow rate: 1.5 mL / min, splitless.

[0087] Mass spectrometry conditions: ion source temperature 230℃, ionization mode EI; quadrupole temperature 150℃; acquisition type: SIM and full scan, scan range mass number 50~800amu; solvent delay 4min.

[0088] Example 3

[0089] The embodiment of the present invention for testing the PC content in PC alloys, the method for testing the PC content in PC alloys, includes the following steps:

[0090] (1) The formulation system of the PC / ABS alloy sample 3 to be tested was confirmed by infrared and XRF testing. The system contains PC, ABS, and Si and P elements. For infrared testing, the sample was prepared by hot pressing film formation method, followed by infrared detection and analysis. The wavenumber range of the analysis was 400 to 4000 cm⁻¹. -1 The resolution is 3-5cm. -1 The number of infrared scans was 16.

[0091] (2) Place 1.0552g of sample into 40g of ethylene glycol under microwave conditions of 500-1000w (automatic adjustment) at 196℃ for catalytic depolymerization for 30min, filter, and obtain a mixture and insoluble matter; add zinc acetate for catalytic depolymerization, with the mass ratio of zinc acetate to sample being 0.005:1.

[0092] (3) Comprehensive analysis: The insoluble matter was washed with methanol multiple times, filtered, dried and weighed to 0.2152g. The infrared spectrum was tested to confirm that the PC depolymerization and separation were complete.

[0093] The mixture was subjected to GC-MS and HPLC tests to detect the qualitative and quantitative analysis of other additives besides PC depolymerization products, namely the flame retardant BDP. The PC content was obtained by subtracting the flame retardant component from the soluble component, thus completing the test of PC content in the PC alloy.

[0094] The PC quantitative analysis consisted of GC MS and HPLC tests; the test conditions were the same as in Example 2.

[0095] Alternatively, the total phosphorus content of the original sample can be calculated by ICP-OES testing to obtain the flame retardant content, which in turn yields the PC content, and thus the total amount of ABS and toughening agent.

[0096] Example 4

[0097] The embodiment of the present invention for testing the PC content in PC alloys, the method for testing the PC content in PC alloys, includes the following steps:

[0098] (1) The formulation system of the PC / ABS alloy sample 4 to be tested was confirmed by infrared and XRF testing. The system contains PC, ABS and Si elements. For infrared testing, the sample was prepared by hot pressing film formation method, and then infrared detection and analysis were performed. The wavenumber range of the analysis was 400 to 4000 cm⁻¹. -1 The resolution is 3-5cm. -1 The number of infrared scans was 32.

[0099] (2) Place 1.0679g of sample into 40g of butanediol under microwave conditions of 500-1000w (automatic adjustment) at 220℃ for catalytic depolymerization for 30min, filter, and obtain a mixture and insoluble matter; add zinc acetate for catalytic depolymerization, with the mass ratio of zinc acetate to sample being 0.01:1.

[0100] (3) Comprehensive analysis: The insoluble matter was washed and filtered with methanol multiple times, dried, and weighed to 0.3609 g. Infrared spectroscopy confirmed complete depolymerization and separation of PC. The PC content could be obtained by subtracting the weight difference, thus completing the test of PC content in the PC alloy.

[0101] Example 5

[0102] The embodiment of the present invention for testing the PC content in PC alloys, the method for testing the PC content in PC alloys, includes the following steps:

[0103] (1) The formulation system of the PC / ABS alloy sample 5 to be tested was confirmed by infrared and XRF testing. The system contains PC and ABS. For infrared testing, the sample was prepared by hot pressing film formation method, and then infrared detection and analysis were performed. The wavenumber range of the analysis was 400 to 4000 cm⁻¹. -1 The resolution is 3-5cm. -1 The number of infrared scans was 16.

[0104] (2) Place 1.0008g of sample into 40g of butanediol and perform alcoholysis catalytic depolymerization at 220℃ for 30min under microwave conditions of 500-1000w (automatic adjustment). Filter to obtain a mixture and insoluble matter. Add tetrabutyl titanate to the alcoholysis catalytic depolymerization. The mass ratio of tetrabutyl titanate to sample is 0.002:1.

[0105] (3) Comprehensive analysis: The insoluble matter was washed and filtered with methanol multiple times, dried, and weighed to 0.9002g. The infrared spectrum was tested to confirm that the PC depolymerization and separation were complete. The PC content can be obtained by subtracting the weight difference, thus completing the test of the PC content in the PC alloy. The total content of ABS and MBS can be obtained by the content of the insoluble matter.

[0106] Example 6

[0107] The embodiment of the present invention for testing the PC content in PC alloys, the method for testing the PC content in PC alloys, includes the following steps:

[0108] (1) The formulation system of the PC / PE alloy sample to be tested was confirmed by infrared and XRF testing. The system contains PC and PE. For infrared testing, the sample was prepared by hot pressing film formation method, followed by infrared detection and analysis. The wavenumber range of the analysis was 400 to 4000 cm⁻¹. -1 The resolution is 3-5cm.-1 The number of infrared scans was 16.

[0109] (2) Place 1.0552g of sample into 40g of butanediol and catalytically depolymerize at 220℃ under microwave conditions of 500-1000w (automatic adjustment) for 30min. Filter to obtain a mixture and insoluble matter. Add zinc acetate to the catalytic depolymerization, with the mass ratio of zinc acetate to sample being 0.005:1.

[0110] (3) Comprehensive Analysis: The insoluble matter was washed repeatedly with methanol, filtered, dried, and weighed to 0.1605 g. Infrared spectroscopy confirmed complete depolymerization and separation of PC. The PC content could be obtained by subtracting the weight difference, thus completing the test of PC content in the PC alloy.

[0111] Example 7

[0112] The embodiment of the present invention for testing the PC content in PC alloys, the method for testing the PC content in PC alloys, includes the following steps:

[0113] (1) The formulation system of the PC / PS alloy sample to be tested was confirmed by infrared and XRF testing. The system contains PC and PP. For infrared testing, the sample was prepared by hot pressing film formation method, followed by infrared detection and analysis. The wavenumber range of the analysis was 400 to 4000 cm⁻¹. -1 The resolution is 3-5cm. -1 The number of infrared scans was 16.

[0114] (2) Place 1.0852g of sample into 40g of ethylene glycol and catalytically depolymerize at 190℃ under microwave conditions of 500-1000w (automatic adjustment) for 60min. Filter to obtain a mixture and insoluble matter. Add zinc acetate to the catalytic depolymerization, with the mass ratio of zinc acetate to sample being 0.005:1.

[0115] (3) After multiple washings and filtrations with methanol, the insoluble matter was dried and weighed to 0.169 g. Infrared spectroscopy confirmed complete depolymerization and separation of PC. The PC content can be obtained by subtracting the weight difference, thus completing the test of PC content in the PC alloy.

[0116] Example 8

[0117] The embodiment of the present invention for testing the PC content in PC alloys, the method for testing the PC content in PC alloys, includes the following steps:

[0118] (1) The formulation system of the recycled PC / ABS alloy sample to be tested was confirmed by infrared and XRF testing. The system contains PC, ABS and a small amount of impurity elements. For infrared testing, the sample was prepared by hot pressing film formation method, followed by infrared detection and analysis. The wavenumber range of the analysis was 400 to 4000 cm⁻¹. -1 The resolution is 3-5cm. -1 The number of infrared scans was 16.

[0119] (2) 2.0143g of sample was placed in 40g of 1,4-butanediol under microwave conditions of 500-1000w (automatic adjustment) for catalytic depolymerization at 220℃ for 30min, filtered, and a mixture and insoluble matter were obtained; zinc acetate was added for catalytic depolymerization, and the mass ratio of zinc acetate to sample was 0.002:1.

[0120] (3) Comprehensive Analysis: The insoluble matter was washed repeatedly with methanol, filtered, dried, and weighed to 0.4380 g. Infrared spectroscopy confirmed complete depolymerization and separation of PC. GC-MS analysis of the alcoholysis solution, after dilution with methanol, revealed the presence of ethylene glycol and dibutyl terephthalate, indicating a small amount of PET impurities in the recycled PC. PET readily undergoes diol hydrolysis. The PET content was calculated by converting the EG content using GC-FID. Subtracting the PET content from the weight difference yielded the PC content, thus completing the PC content test in the PC alloy.

[0121] Simultaneously, the actual PET content in recycled PC was detected, revealing that the actual PC ratio in recycled PC / ABS was 70%.

[0122] GC-FID testing conditions: Analysis was performed using an Anglient 7697A / 7890A gas chromatograph. The chromatographic column was a DB-WAX, 30m × 250μm ID × 0.25μm quartz capillary column. The injection port temperature was 250℃, the column temperature was maintained at 45℃ for 2 min, then increased at 20℃ / min to 195℃ and maintained for 2 min, then increased at 20℃ / min to 230℃ and maintained for 2 min. The flame ionization detector (FID) temperature was 250℃, H2: 30 mL / min, air: 400 mL / min.

[0123] In the detection of each embodiment, the steps of PC quantitative analysis are as follows: the mass of the PC alloy sample to be tested before and after alcoholysis catalytic depolymerization is counted, the content of substances dissolved in the mixed solution of the PC alloy sample to be tested is calculated, the content of substances other than PC is detected by HPLC or LC-MS, and finally the content of PC in the PC alloy sample to be tested is calculated. The results are shown in Table 1.

[0124] Comparative Example 1

[0125] The existing TGA residual carbon method for determining the PC content in PC alloys includes the following steps:

[0126] The PC / ABS alloy sample 1 was placed in a thermogravimetric analyzer and heated from 30°C to 600°C at a rate of 20°C / min under a nitrogen atmosphere. At 600°C, the temperature was switched to an air atmosphere, and the temperature was increased to 800°C. The PC content % of the sample was calculated as: (Weight loss due to air switching / Weight loss rate of pure PC after air switching) * 100%.

[0127] Comparative Example 2

[0128] The existing TGA residual carbon method for detecting PC content in PC alloys differs from Comparative Example 1 only in that PC / ABS alloy 1 is replaced by PC / ABS alloy 2.

[0129] Comparative Example 3

[0130] The existing TGA residual carbon method for detecting PC content in PC alloys differs from Comparative Example 1 only in that PC / ABS alloy 1 is replaced by PC / ABS alloy 3.

[0131] Comparative Example 4

[0132] The existing TGA residual carbon method for detecting PC content in PC alloys differs from Comparative Example 1 only in that the PC / ABS alloy 1 is replaced with a recycled PC / ABS alloy.

[0133] Comparative Example 5

[0134] Existing FTIR methods for determining PC content in PC alloys include the following steps:

[0135] The characteristic peaks 1773 / 700CM of PC / ABS alloys with different known ratios were selected. -1 A quantitative model for the content was established, and the ratio of the characteristic peaks of the functional groups of PC / ABS alloy 1 was substituted into the model to calculate the content of PC.

[0136] Comparative Example 6

[0137] The existing FTIR method for detecting PC content in PC alloys differs from Comparative Example 5 only in that PC / ABS alloy 1 is replaced with PC / ABS alloy 2.

[0138] Comparative Example 7

[0139] The existing FTIR method for detecting PC content in PC alloys differs from Comparative Example 5 only in that PC / ABS alloy 1 is replaced by PC / ABS alloy 3.

[0140] The test results for each comparative example are shown in Table 1.

[0141] Table 1

[0142]

[0143]

[0144] As can be seen from Table 1, the method described in this invention can test the PC content of PC alloy products of various systems, and the deviation between the test results and the actual results can be controlled within 3%, demonstrating extremely high accuracy. Furthermore, comparing the initial infrared spectra of the samples from Examples 1 and 2 with the infrared spectra of the remaining insoluble matter after microwave catalytic depolymerization shows... Figures 1-2 As shown, the insoluble substances are essentially free of PC, consisting mainly of ABS resin and components such as toughening agents. This indicates that the microwave-catalyzed depolymerization treatment described in this invention can effectively and selectively separate PC from the product. A comparison of the results from Examples 1-3 and Comparative Examples 1-3 and 5-7 shows that, for different PC / ABS alloy samples, the commonly used TGA carbon residue method and FTIR method exhibit significant detection errors, with accuracy far lower than the method described in this invention. Furthermore, the results from Example 8 and Comparative Example 4 demonstrate that when the test object is replaced with an alloy product containing recycled PC, the method described in this invention still shows a significant improvement in accuracy compared to existing technologies. It does not experience a decrease in accuracy due to impurities or changes in molecular chain segments contained in the recycled PC, exhibiting a smaller relative deviation.

[0145] Subsequently, based on Example 1, to explore the process specificity of the microwave catalytic depolymerization treatment, the following settings were made:

[0146] The control groups 1-4 differed from Example 1 only in that the 1,4-butanediol used in the microwave catalytic depolymerization was replaced with methanol, glycerol, chloroform, and tetrahydrofuran, respectively, and carried out at room temperature; all other aspects remained unchanged.

[0147] The control groups 5-7 differed from Example 1 only in that the temperatures and times during alcoholysis catalytic depolymerization were 150℃ (30 min), 150℃ (60 min), and 250℃ (10 min), respectively.

[0148] The control group 8 differed from Example 1 only in that step (2) was as follows: 1.0888g of sample was placed in 40g of 1,4-butanediol, heated in an oil bath to 220°C for 30 minutes for alcoholysis catalytic depolymerization, filtered to obtain a mixture and insoluble matter; zinc acetate was added for alcoholysis catalytic depolymerization, and the mass ratio of zinc acetate to sample was 0.005:1.

[0149] Subsequently, the weight of insoluble matter obtained from each control group was counted, and infrared testing was used to confirm the depolymerization and separation of PC.

[0150] The test results are shown in Table 2.

[0151] Table 2

[0152]

[0153]

[0154] As can be seen from the table, not all reagents used in the prior art for dissolving PC can be used for the selective dissolution of the PC alloy described in this invention. Some conventional reagents for dissolving PC will dissolve both PC and ABS in the PC alloy, making it impossible to separate them for comprehensive analysis. Due to the special properties of PC, the method described in this invention requires the use of specific alcohols for depolymerization and separation. Diols are most effective in the depolymerization process, resulting in more accurate measurement results. Some monools such as methanol and ethanol, or other diols, cannot achieve good PC depolymerization under the conditions described in this invention, requiring methods such as supercritical treatment to achieve the same effect, which is cumbersome and complex. Furthermore, the alcoholysis of glycerol cannot achieve complete depolymerization at room temperature, but at high temperatures, it is known that other substances in the test sample besides PC will also begin to decompose, making it impossible to accurately determine the PC content of the sample. In the alcoholysis process described in this invention, if the temperature is insufficient, even with prolonged treatment, sufficient depolymerization of PC in the sample cannot be achieved, leading to large deviations in the detection results. Simultaneously, attention must be paid to the boiling point of the depolymerization alcohol used to avoid boiling over during heating. In control group 8, microwave-assisted heating was not used; instead, heating was performed directly in an oil bath. The results show that, under the same conditions, this step was not ideal for depolymerizing PC in the sample.

[0155] Example of effect 1

[0156] To illustrate the practicality of the method described in this invention, this method was used to test a PC alloy sample with an unknown composition, including the following steps:

[0157] (1) The infrared spectrum of the unknown sample was tested, and the test result image showed a value of 1773 cm⁻¹. -1 The characteristic peak of PC has a 700 cm⁻¹ -1 760cm -1 2234cm -1 The characteristic peak of ABS is 3676 cm⁻¹. -1 and 1016cm -1 Characteristic peaks of talc indicated that the unknown sample was a PC / ABS talc-filled system. XRF testing revealed that the sample mainly contained silicon, magnesium, bromine, and antimony, further confirming the presence of talc and bromine-antimony flame retardant. Simultaneously, PYGC-MS analysis of the original sample revealed that the main fragments included butadiene, styrene, methyl methacrylate, butadiene dimer 4-vinyl-1-cyclohexene, bisphenol A, and tetrabromobisphenol A.

[0158] (2) Place 1.0568g of sample into 40g of butanediol and perform alcoholysis catalytic depolymerization at 220℃ for 30min under microwave conditions of 500-1000w (automatic adjustment). Filter to obtain a mixture and insoluble matter. Add zinc acetate to the alcoholysis catalytic depolymerization. The mass ratio of zinc acetate to sample is 0.005:1.

[0159] (3) Comprehensive Analysis: The insoluble matter was washed and filtered multiple times with methanol, dried, and weighed to 0.3170 g. Infrared spectroscopy confirmed complete depolymerization and separation of PC. The insoluble components were mainly ABS, acrylate copolymers, and inorganic substances. The washing solution and alcoholysis solution were collected, diluted with methanol, and tested by GC-MS. Tetrabromobisphenol A, antioxidant 1076, and antioxidant 168 were found. The contents of tetrabromobisphenol A and antioxidants were accurately quantified using pre-established external standard lines for tetrabromobisphenol A and antioxidants by GC-MS.

[0160] The total amount of inorganic and organic matter was obtained by using a TGA chromatogram of the original sample. The content of antimony trioxide was calculated by using an ICP test.

[0161] The test results of the unknown samples obtained through comprehensive analysis are shown in Table 3.

[0162] Table 3

[0163]

[0164] Meanwhile, the same sample was tested using the commonly used TGA residual carbon method described in Comparative Example 1. The results showed that the PC content was 50%, which is significantly different from the method described in this invention.

[0165] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for testing the PC content in a PC alloy, characterized in that, Includes the following steps: (1) The formulation system of the PC alloy sample to be tested was confirmed by infrared and XRF testing; The formulation system contains PC resin, compound resin, and antioxidant; (2) Place the PC alloy sample to be tested into a diol containing a catalyst and perform alcoholysis catalytic depolymerization at 180~235℃ for 10~65 min under microwave conditions, filter, and obtain a mixture; (3) Comprehensive analysis: The mixture is subjected to quantitative analysis of other additives besides PC depolymerization products. The test of PC content and other additive content in PC alloy is completed through comprehensive analysis. The comprehensive analysis steps include: statistically analyzing the mass of the PC alloy sample before and after alcoholysis catalytic depolymerization, calculating the content of substances dissolved in the mixed solution of the PC alloy sample, using HPLC and / or LC-MS to detect the content of other additive substances besides PC depolymerization products, and finally calculating the PC content in the PC alloy sample. The calculation formula is: PC content in the PC alloy sample to be tested = 100% × (initial mass of the PC alloy sample to be tested before alcoholysis catalytic depolymerization - mass of insoluble matter after alcoholysis catalytic depolymerization of the PC alloy sample to be tested - mass of other additive substances dissolved after alcoholysis catalytic depolymerization of the PC alloy sample to be tested) / initial mass of the PC alloy sample to be tested before alcoholysis catalytic depolymerization.

2. The method for testing the PC content in a PC alloy as described in claim 1, characterized in that, The PC alloy sample to be tested is at least one of virgin material and recycled material.

3. The method for testing the PC content in a PC alloy as described in claim 2, characterized in that, The PC alloy sample to be tested contains ≥5 wt% PC.

4. The method for testing the PC content in a PC alloy as described in claim 3, characterized in that, The compounded resin is at least one of ABS resin, PE resin, PP resin, POM resin, and PS resin; the PC alloy is at least one of PC / ABS alloy, PC / PE alloy, PC / PP alloy, PC / POM alloy, and PC / PS alloy.

5. The method for testing the PC content in a PC alloy as described in claim 1, characterized in that, The diol is at least one of ethylene glycol, butanediol, and 1,2-propanediol, and the mass ratio of the diol to the PC alloy sample to be tested is (5~42):

1.

6. The method for testing the PC content in a PC alloy as described in claim 1, characterized in that, The catalyst used in the alcoholysis catalytic depolymerization is at least one of zinc acetate, potassium acetate, tetrabutyl titanate, sodium carbonate, sodium hydroxide, zinc oxide, and potassium hydroxide. The mass ratio of the catalyst to the PC alloy sample to be tested is (0.001~0.01):

1.

7. The method for testing the PC content in a PC alloy as described in claim 1, characterized in that, The power of the microwave is 500~1000W.

8. The method for testing the PC content in a PC alloy as described in claim 1, characterized in that, The test conditions for the HPLC test are as follows: Column: Waters Symmetry C18; Column temperature: 30~40℃; Flow rate: 0.5~1.5 mL / min; Injection volume: 8~12μL; Mobile phase A is methanol, and mobile phase B is water; The mobile phase isocratic elution program is: 90.0% methanol, 10.0% water.